Rethinking neoadjuvant chemotherapy for breast cancer. (11th January 2018) - Vaidya, Jayant S; Massarut, Samuele; Vaidya, Hrisheekesh J; Alexander, Emma C; Richards, Thomas; Caris, Jochem A; Sirohi, Bhawna; Tobias, Jeffrey S
Abstract : As evidence questioning the rationale behind neoadjuvant chemotherapy in breast cancer grows, Jayant Vaidya and colleagues say we must reconsider the current treatment options